2007
DOI: 10.1007/s10802-006-9075-2
|View full text |Cite
|
Sign up to set email alerts
|

Restraint and Cancellation: Multiple Inhibition Deficits in Attention Deficit Hyperactivity Disorder

Abstract: We used variations of the stop signal task to study two components of motor response inhibition-the ability to withhold a strong response tendency (restraint) and the ability to cancel an ongoing action (cancellation)-in children with a diagnosis of attention deficit hyperactivity disorder (ADHD) and in non-ADHD controls of similar age (ages 7-14 years). The goal was to determine if restraint and cancellation were related and if both were deficient in ADHD. The stop signal task involved a choice reaction time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
189
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(206 citation statements)
references
References 67 publications
12
189
1
4
Order By: Relevance
“…Finally, Schachar et al (2007) found a dissociation between nogo performance and stop performance in children with ADHD but not in healthy control children.…”
Section: The Stop-signal and Go/nogo Paradigmmentioning
confidence: 84%
“…Finally, Schachar et al (2007) found a dissociation between nogo performance and stop performance in children with ADHD but not in healthy control children.…”
Section: The Stop-signal and Go/nogo Paradigmmentioning
confidence: 84%
“…cocaine, amphetamine, methamphetamine), and is also seen as a useful behavioural marker of genetic risk factors (Aron 2007;Aron and Poldrack 2005;Bellgrove et al 2006;Durston et al 2008;Fillmore et al , 2006Gauggel et al 2004;Monterosso et al 2005;Nigg et al 2004;Oosterlaan et al 1998;Penades et al 2007;Rubia et al 1998Rubia et al , 2005bRubia et al , 2007Schachar et al 2007;Schachar et al 1995;van den Wildenberg et al 2006). Indeed, impaired action inhibition is often considered as the core deficit in ADHD (e.g.…”
Section: The Unitary Concept Of 'Action Inhibition'mentioning
confidence: 99%
“…Recently, Schachar et al (2007) defined two forms of action inhibition: 'action restraint' and 'action cancellation'. With both forms of inhibition acting on pre-planned motor actions, action restraint describes the inhibition of the motor response before that response has been started.…”
Section: 'Action Restraint' and 'Action Cancellation'mentioning
confidence: 99%
See 2 more Smart Citations